Numerical Study of Savonius Wind Turbine with Fluid-Rotor Interactions - Zain Lillahulhaq; Vivien Suphandani Djanali (Institut Teknologi Sepuluh Nopember, 2019)
Previous numerical studies in the Savonius wind turbine mostly used constant angular velocity as input data, where the values were obtained from experiments. This process cannot be used in the design optimization of the turbine, in which the angular velocity of the modified turbine is not known a priority. In numerical simulation, the use of loading system to get constant angular velocity to control the tip speed ratio (TSR), tends to have fluctuating value on output data. Moreover, the values of angular velocity shall be the results from freestream flow and Savonius rotor interaction. This condition can be simulated by using fluid structure interaction (FSI) method. Three dimensional Savonius S wind turbine is simulated using unsteady Reynolds Averaged Navier Stokes (RANS). Inlet velocity and wind turbine inertia are used as input data. The flow is assumed to be incompressible, viscous, and uniform at the inlet. The turbulence model used is the Eddy Viscosity k-ω SST, with y+ < 1. The domain consists of a sliding mesh, which rotates in the overset mesh region. Simulation results Power Coefficient (CP) and angular velocity and compared with experimental result. This study is resulted a standard method for the Savonius wind turbine numerical study